Peran Rumah Baca Rumbai Dalam Meningkatkan Literasi Membaca Masyarakat Kota Jambi Tahun 2024 - Nurpadilla, Nurpadilla (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2024)
This research discusses the role of the Rumbai Reading House in increasing the reading literacy of the people of Jambi City. The main discussion in this research is about the role of the Rumbai Reading House in improving literacy in the community, which has been established since 2015. This research uses qualitative methods with data collection techniques through observation, interviews and documentation. The informants in this Reading House are the Chair of the Reading House, its members and the community. To measure data validation, triangulation is used. First, the role of the Reading House in Reading Literacy Activities. Community Recognizes Asam Atas RT 14 Kec, Kota Baru, Jambi City. Viewed from three aspects: (1) Sources of Information The sources of information owned by the Rumbai Reading House can help visitors fulfill their information needs, both formal and informal. (2) When visiting the community, visits to the Rumbai Reading House appear to be lacking. , only a few people came to visit. This shows that there is less interest in visiting the Rumbai Reading House. (3) Interest in Reading shows that efforts to increase interest in reading in the RT 14 Kenali Asam community need to pay attention to children's preferences for other educational media, such as educational films, as well as designing literacy strategies or programs that are interesting and relevant for them, so that interest in reading can be achieved. increases. (4) the guiding media for the Rumbai Reading House community is considered as a place that acts as a medium or bridge to connect sources of information and knowledge with visitors and themselves. (5) The literacy movement of the Rumbai Reading House community acts as a measure or barometer for development In community literacy activities, they really understand how to use social media wisely without using fake news. Second, the inhibiting factors found include a lack of human resources, budget funds, lack of public awareness, and inadequate collections. Meanwhile, the supporting factors at the Rumbai Reading House include the strategic location of the Reading House and supporting facilities. Third, the efforts made by the Rumbai Reading House in reading literacy activities for the people of Jambi City Keywords: Role of Libraries, Reading Literacy, Socie